Akt in cancer: Mediator and more. (December 2019) - Revathidevi, Sundaramoorthy; Munirajan, Arasambattu Kannan
Abstract: Akt is a serine/threonine kinase and it participates in the key role of the PI3K signaling pathway. The Akt can be activated by a wide range of growth signals and the biochemical mechanisms leading to Akt activation are well defined. Once activated, Akt modulates the function of many downstream proteins involved in cellular survival, proliferation, migration, metabolism, and angiogenesis. The Akt is a central node of many signaling pathways and it is frequently deregulated in many types of human cancers. In this review, we provide an overview of Akt function and its role in the hallmarks of human cancer. We also discussed various mechanisms of Akt dysregulation in cancers, including epigenetic modifications like methylation, post-transcriptional non-coding RNAs-mediated regulation, and the overexpression and mutation.